Efektifitas Pijat Oksitosin terhadap Produksi Air Susu Ibu (ASI) pada Ibu Post Partum Sectio Caesaria (SC) di Ruang Kalimaya Bawah RSUD dr. Slamet Garut - Gin Gin Sugih Permana; Kurniawan Dewi Budiarti; Tantri Puspita (STIKes Karsa Husada Garut, 2018)
Infant Mortality Rate (IMR) is caused by a lack of exclusive breast feeding. One of them due to the lack of production of breast milk on the first day after delivery that can be caused by a lack of stimulation oxytocin and prolactin hormon.There are two hormones that essential to producebreast milk.For expenditure nonfarmakologis effort is needed in the form of oxytocin breast massage. Oxytocin massage is very helpful in the process of spending on breast milk. Objectivesi is To find out the effectiveness of massage oxytocin breast milk production in the mother against the post partum in the Kalimaya Bawah Hospital Dr. Slamet Garut the year 2018. The Methods used is the study was hised quasy experimentsmethod with pretest-posttest with Control group, the study was carried out during the 30 days of sampling technique with